Efforts to Improve Achievement of Middle-School Students in Lower Passing Volleyball Games Through Wall Media - Saputra, Eeng Diah; La Kamadi; Haeruddin, Sofyan (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This study aims to describe the planning, implementation, observation, reflection, and application of wall media in an effort to improve the learning outcomes of down passing in volleyball games for seventh-grade students at MTSN 4 Banyuwangi. This research consists of two cycles. In each cycle, there are four stages, namely planning, implementation, observation, and reflection. The data of this research is the ability to pass down as psychomotor data and the value of practice questions as cognitive value and observation as affective value. The subjects of this study were students of class VII MTSN 4 Banyuwangi, as many as 30 students, with details of 13 male students and 17 female students. Based on the results of the quantitative analysis of the data on the bottom passing learning outcomes, it shows that the students who completed the first cycle were 14 people, with a percentage of 46%, while the number of students who completed the second cycle was 28 people, with a percentage of 93%. Based on the results of this study, it can be concluded that the learning of under passing through the wall media can improve the learning outcomes of under passing in the volleyball game for class VII MTSN 4 Banyuwangi students.